The episteme of happiness as ontological vertical in modern education: The maslow answer - Wen Heng Fu; Satrianawati Satrianawati (International Journal of Education and Learning, 2020)
The article deals with the analysis of the Maslow's ontological level answer of happiness in modern education, which forms the perspectives of development and the modern cultural core of social life. As a prerequisite for the analysis, theory Maslow about the hierarchy of needs as the ontological foundations of happiness in modern education. The methodological basis of the research made is mix-method. This research takes sixty-one participants in the survey and using interviews to strengthen data in descriptive qualitative. It established the episteme sources of Maslow's works. The results of this analysis have projected onto the current situation in modern education. This projection's ontological components are the correlation of happiness with the hierarchy of needs, a combination of theoretical understanding and get happiness, value mediation of Maslow's theory to innovate modern education. Having examined the hierarchy of needs meanings, the author shows the perspectives of the enhanced comprehension of modern education and Maslow's theory. The vertical of the paradigmatically-differentiated hierarchy of needs in modern education development has been considered the place of cognitive-cultural diversity. The characteristic is given of the episteme of activity to achieve happiness in the focus of research education.